THE EFFECT OF SUBJECTIVE NORMS, MORAL OBLIGATIONS AND SANCTIONS ON TAX COMPLIANCE FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN SOUTH MAKASSAR KPP - Yahya, Muhammad; Mahmuddin, Mahmuddin; Pahrul, Pahrul; Bustam, Bustam (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
This study aims to determine the influence of subjective norms, moral obligations, and tax sanctions on taxpayer compliance. The population in this study is MSME taxpayers registered with KPP Pratama South Makassar. Sampling was carried out by incidental sampling technique. Data analysis techniques are carried out by descriptive statistical analysis and SPSS (Statistical Product and Service Solution). Based on the analysis that has been carried out, subjective norms have a positive and significant effect on taxpayer compliance. Moral obligations have a positive and significant effect on taxpayer compliance. Tax sanctions have a positive and significant effect on taxpayer compliance.Keywords: Subjective Norms, Moral Obligations, Tax Sanctions, Taxpayer Compliance.